Evolutionary drivers of temporal and spatial host use patterns in restio leafhoppers Cephalelini (Cicadellidae) - Augustyn, Willem Johannes (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.